Speaking Up, Pushing Back, Closing the Door: Agency of Open and Covert Teacher Resistance in Dual-Language Bilingual Education - Brandon Sherman; Trish Morita-Mullaney; Jennifer Renn (AERA Open)
The increasing prominence of dual-language bilingual education (DLBE) in the United States necessitates deeper understanding of institutional roles and professional identities of DLBE teachers, particularly when incongruent. We qualitatively analyzed teacher resistance in discordant situations as discussed in conferences between DLBE teachers and a bilingual instructional coach in two districts over 2 years. In these conversations, we found a distinction between nonconfrontational and open, direct resistance. We applied an agentive triad model of teacher identity, agency, and power to understand how DLBE teachers navigated discordant situations in their schools. Teachers acted from different identity positions, including agentive compliance, anagentive compliance (without agency), and nonconfrontational resistance. Findings and theorization demonstrate that DLBE programs present special considerations for teacher identity, role, and resistance. Moreover, context-specific characteristics, including program age, model, and administration, may impact teachers’ approach to resistance. Findings and theorization are relevant to successful DLBE program implementation and equity focused instructional coaching.